1997
DOI: 10.1063/1.119050
|View full text |Cite
|
Sign up to set email alerts
|

Colossal magnetoresistance in epitaxial La(1−x−y)NayMnO3 thin film

Abstract: We have synthesized La0.83Na0.11MnO2.93 by heating La2O3 and MnCO3 in NaCl melt at 900 °C. The exact composition was arrived by analyzing each ion by an independent chemical method. The compound crystallized in a rhombohedral structure and showed an insulator-to-metal transition at 290 K. Epitaxial thin films were fabricated on LaAlO3 (100) using a pulsed laser deposition technique. The film also showed an insulator-to-metal transition at 290 K. Magnetoresistance [ΔR/R0=(RH−R0)/R0] was −71% near the insulator-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 12 publications
1
28
1
Order By: Relevance
“…Moreover, as the milling time increases, the T IM is decreased and the resistivity is continuously increased, which can be attributed to the decrease of the crystalline size [11,12,20,21]. From Table 1, it can be observed that the T IM of the sample MA0 is about 270 K, which is lower than that of the previously reports and it may be related to the smaller crystalline size in our experiment [23][24][25][26][27]. As for the origin of the decrease of the T IM and the increase of the resistivity, the reason is discussed as follows.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Moreover, as the milling time increases, the T IM is decreased and the resistivity is continuously increased, which can be attributed to the decrease of the crystalline size [11,12,20,21]. From Table 1, it can be observed that the T IM of the sample MA0 is about 270 K, which is lower than that of the previously reports and it may be related to the smaller crystalline size in our experiment [23][24][25][26][27]. As for the origin of the decrease of the T IM and the increase of the resistivity, the reason is discussed as follows.…”
Section: Resultscontrasting
confidence: 72%
“…Unlike divalent element-doped manganites, the monovalent elementdoped manganites have some interesting features. One of the most important features is that it is possible to achieve an equal amount of holes with a lower cation substitution for La sites, which will result in lower cation disorder [23,24]. In the monovalent element-doped manganites, the La 1−x Na x MnO 3 is a typical system and it has relatively large MR values near room temperature [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Since Na or K can substitute for La (13), we obtained ferromagnetic Na or K doped lanthanum manganites. Among the large number of Na or K doped lanthanum manganites synthesized by this method, epitaxial thin film of La Na MnO was made by pulsed laser deposition, and the thin film showed over 70% CMR at 290 K in 6T magnetic field (14). Composition of these phases has been derived by chemical analysis of La, Na/K, Mn, and oxygen independently.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difference in valence states, the divalent and the monovalent ion doping in LaMnO 3 can result in different consequences. In both the monovalent and the divalent ion doping manganites similar electrical and magnetic properties are obtained [6][7][8][9][10][11], but usually the monovalent ion doped mangnites have a higher T C [8], which is important when considering the practical application of these kinds of materials. In the magnetoresistance materials, the CMR is generally associated with a phase transition (I-M, PM-FM).…”
Section: Introductionmentioning
confidence: 99%